ASPECTS OF ADAPTATION TO DENTURES AND USING DRUGS CORRECTLY (Intent Research Scientific Journal, 2023)
The process of adaptation to dentures in patients is influenced by local and systemic factors. The data on the influence of the type of higher nervous activity on the process of adaptation to dentures and on the temporal and physiological characteristics of the formation of an adaptive response are presented. The results of experimental and clinical studies of the effect of local and systemic use of drugs of various pharmacotherapeutic groups on the parameters of adaptation of patients to dental structures are analyzed. The effectiveness of the use of drugs with stress-protective, antioxidant and antitoxic effects was noted.